Beethoven portrait by Crane based on Jäger - Crane, S.W. (artist):::Creator::::::::::::; Jäger, Carl, 1833-1887:::Contributor:::::::::::: (New York; United States; Joseph Patelson Music House)
Lithograph portrait of Beethoven, possibly based on a portrait by Carl Jäger from 1870.